Artemisia argyi attenuates airway inflammation in ovalbumin-induced asthmatic animals. (14th September 2017) - Shin, Na-Rae; Ryu, Hyung-Won; Ko, Je-Won; Park, Sung-Hyeuk; Yuk, Heung-Joo; Kim, Ha-Jung; Kim, Jong-Choon; Jeong, Seong-Hun; Shin, In-Sik
Abstract: Ethnopharmacological relevance: Artemisia argyi is a traditional herbal medicine in Korea and commonly called as mugwort. It is traditionally used as food source and tea to control abdominal pain, dysmenorrhea, uterine hemorrhage, and inflammation. Aim of the study: We investigated the effects of A. argyi (TOTAL) and dehydromatricarin A (DA), its active component on ovalbumin (OVA)-induced allergic asthma. Materials and methods: The animals were sensitized on day 0 and 14 by intraperitoneal injection of OVA with aluminum hydroxide. On day 21, 22 and 23 after the initial sensitization, the animals received an airway challenge with OVA for 1 h using an ultrasonic nebulizer. TOTAL (50 and 100 mg/kg) or DA (10 and 20 mg/kg) were administered to mice by oral gavage once daily from day 18–23. Airway hyperresponsiveness (AHR) was measured 24 h after final OVA challenge. Result: TOTAL and DA treated animals reduced inflammatory cell counts, cytokines and AHR in asthmatic animals, which was accompanied with inflammatory cell accumulation and mucus hypersecretion. Furthermore, TOTAL and DA significantly declined Erk phosphorylation and the expression of MMP-9 in asthmatic animals. Conclusion: In conclusion, we indicate that Total and DA suppress allergic inflammatory responses caused by OVA challenge. It was considered that A. argyi has a potential for treating allergic asthma. Graphical abstract: